Anxiety and mental toughness in football players: a study of the Kerala Premier League and women's Kerala Premier League - Ajmal PM; Sivachandiran S; Ashif Ali NK; Safad AK; Dilshith Azeezul Kabeer; Vinu W (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Competitive anxiety and mental toughness are critical psychological factors influencing athletic performance. However, research on these traits among professional footballers in regional leagues like the Kerala Premier League (KPL) and Women's Kerala Premier League (WKPL) remains limited. Under-standing gender differences and the role of competitive experience can inform targeted mental training strategies. Objective: This study ex-amined gender differences in sports competitive anxiety and mental toughness among professional foot-ballers in the KPL and WKPL. It also explored the relationship between competitive experience, anxiety, and mental toughness. Methodology: A cross-sectional, quantitative design was employed. Using purposive sampling, 64 professional footballers (32 males from KPL and 32 females from WKPL) aged 17–24 years with at least one year of competitive experience were selected. Standardized psychological assessments measured sports competitive anxiety and mental toughness. Independent samples t-tests analyzed gender differences, while Pearson correlation assessed associations between experience, anxiety, and mental toughness. Statistical significance was set at p < .001. Results: Female players exhibited higher competitive anxiety, while male players demonstrated greater mental toughness. Competitive experience correlated with lower anxiety and higher mental toughness. A significant inverse relationship was observed between anxiety and mental toughness. Conclusion: The findings highlight gender disparities in psychological resilience, underscoring the role of experience in reducing anxiety and enhancing mental toughness. Struc-tured, gender-specific psychological interventions are essential for optimizing football per-formance in regional leagues.